Structural damage identification based on gray cloud rule generator algorithm - Hui-Yong Guo; He-Fa Yuan; Qi Huang (Advances in Mechanical Engineering, 2019)
It is difficult for the traditional methods to identify uncertain damage problems caused by noise. Therefore, a gray cloud rule generator algorithm based on cloud model and modal strain energy is presented to solve the problems. Cloud model can simulate both randomness and fuzziness with fixed parameters. Therefore, it is applicable for the uncertain damage problems. First, modal strain energy and modal strain energy dissipation ratio index are introduced. Then, numerical characteristics of a cloud model are described and some cloud generators are analyzed. Finally, a gray cloud rule is proposed and the gray cloud rule generator algorithm based on the gray cloud rule generator and modal strain energy is developed. The interference of uncertain noise is reduced through a large number of cloud droplets. A two-dimensional truss structure model has been used to verify the effectiveness of the algorithm. The results indicate that the proposed gray cloud rule generator algorithm is applicable to identify the uncertain damage caused by noise, and the identification results of the proposed method are relatively better than those of modal strain energy dissipation ratio index.